A simulation method for the dissolution construction of salt cavern energy storage with the interface angle considered. (15th January 2023) - Ling, Daosheng; Zhu, Song; Zheng, Jianjing; Xu, Zijun; Zhao, Yunsong; Chen, Liuping; Shi, Xilin; Li, Jinlong
Abstract: The solution mining of a salt cavern for energy storage is highly affected by the interface angle, especially in a horizontal cavern, which has drawn much attention recently. Current empirical models assume the dissolution rates at different angles relate to that of a vertical interface. At the same time, the actual salt cavern design practice has found different conclusions. In this paper, a coupled convection-mass transfer model of rock salt dissolution is developed employing COMSOL software, and the dissolution of salt surfaces with 9 different angles is simulated. In the simulation, the quantitative dissolution rates are consistent with the indoor tests in the literature. The interface angle indirectly influences the dissolution rate through the flow pattern and rate. With larger interface angles, the gravity-driven natural convection gets more intense (no flow at 0°, stream at 45°, waterfall at 90°, raindrop mixing with stream above 90°, totally raindrop at 180°), which means the mass transfer near the boundary gets faster. Thus, the concentration near the boundary decreases, the concentration gradient increases, and the dissolution rate increases. Accordingly, we believe that the angle effect on the dissolution rate is not fixed, possibly being affected by other dissolution convection or the injection-discharge flow cycle. Take the ratio of the upward dissolution rate (α = 180°) and the lateral dissolution rate (α = 90°) (R) as an example, in the previous individual simulations, R is 2. While in the cases of simultaneous upward and lateral dissolution simulation & experiments, the lateral dissolution is accelerated by the global convection flow driven by the upward dissolution, and R is 1.5 & 1.6. In the case of simultaneous multi-angle dissolution, R is 1.3. Therefore, we suggest using the proposed simulation method to help determine the actual dissolution rate in different stages during the design for actual engineering. Highlights: A coupled convection-mass transfer model of salt cavern dissolution is developed. The model is verified by comparison with indoor experiments and field caverns. Interface angle indirectly affects the dissolution rate through convection state. The influencing law changes when the convection state is affected by other factors. We suggest using the proposed method for better salt cavern design.